Distracted from meaning a philosophy of smartphones - Roholt, Tiger C. (Bloomsbury Academic, 2023)
"When our smartphones distract us, much more is at stake than a momentary lapse of attention. Our use of smartphones can interfere with the building-blocks of meaningfulness and the actions that shape our self-identity. By analyzing social interactions and evolving experiences, Roholt reveals the mechanisms of smartphone-distraction that impact our meaningful projects and activities. Roholt's conception of meaning in life draws from a disparate group of philosophers - Susan Wolf, John Dewey, Hubert Dreyfus, Martin Heidegger, and Albert Borgmann. Central to Roholt's argument are what Borgmann calls focal practices: dinners with friends, running, a college seminar, attending sporting events. As a recurring example, Roholt develops the classification of musical instruments as focal things, contending that musical performance can be fruitfully understood as a focal practice. Through this exploration of what generates meaning in life, Roholt makes us rethink the place we allow smartphones to occupy in the everyday. But he remains cautiously optimistic. This thoughtful, needed interrogation of smartphones shows how we can establish a positive role for technologies within our lives"-- Provided by publisher.